The Reveal of Organizational Culture in Big Data-Based Organizations - Setyowati, Ani; Hanifah, Risti Ulfi; Widyakto, Adhi (Management Analysis Journal, 2021)
The key success of an organization's business cannot be separated from the culture that develops in organization. Therefore, organizational culture as a set of values and rules plays very important to build organizational identity. Organizational culture can be designed through the technology which applied in the organization, because technology can be shaped the organizational structure. The purpose of this study is to reveal how far the organizational culture in an organization based on big data technology are formed. This analyzed uses the phenomenological method, focused in electric power services company, precisely at PT. Serkolinas. Data analysis was obtained through field observations and a number of unstructured interviews with a number of eight informants. The results showed that organizational culture can be formed through the technology applied in the organization. Technology as a suggestion in facilitating activities to encourage the perception and behavior of organizational members into a new symbol expressed in daily activities to support of organizational goals..